MP 7 Conversion disorder. Issue 10 (7th September 2012) - Carson, A
Abstract : My interest in neuropsychiatry began during a spell working in Kenya as a Wellcome Research Registrar conducting a study on the psychiatric and cognitive effects of HIV infection. I then completed my higher training in Edinburgh, under the guidance of Professors Michael Sharpe and Charles Warlow, where I developed an interest in functional neurological symptoms. I currently work as a Consultant Neuropsychiatrist in Edinburgh split between the brain injury units at the Astley Ainslie Hospital and the Regional Neurosciences Unit at the Western General Hospital. My collaboration with Michael and Charles has continued and I hold a post as part time Senior Lecturer at Edinburgh University where, along with Dr Jon Stone, we are engaged in the Scottish Neurological Symptoms Study a multi-centre, prospective cohort study of 4000 new neurology outpatients examining the outcome of functional neurological symptoms. This brief review of recent scientific papers on conversion disorders aims to describe some key contributions to the literature over the last 5 years across a range of disparate investigatory techniques. I hope to provide an account of the most recent findings of relevance to diagnosis, underpinning mechanisms, risks factors and treatment. A reference list of papers described will be posted on the BNPA website.